Characterization, Biocompatibility and Antioxidant Activity of Hydrogels Containing Propolis Extract as an Alternative Treatment in Wound Healing - Lindalva Maria de Meneses Costa Ferreira; Yuri Yoshioka Modesto; Poliana Dimsan Queiroz de Souza; Fabiana Cristina de Araújo Nascimento; Rayanne Rocha Pereira; Attilio Converti; Desireé Gyles Lynch; Davi do Socorro Barros Brasil; Edilene Oliveira da Silva; José Otávio Carréra Silva-Júnior; Roseane Maria Ribeiro-Costa (MDPI AG, 2024)
Hydrogels consist of a network of highly porous polymeric chains with the potential for use as a wound dressing. Propolis is a natural product with several biological properties including anti-inflammatory, antibacterial and antioxidant activities. This study was aimed at synthesizing and characterizing a polyacrylamide/methylcellulose hydrogel containing propolis as an active ingredient, to serve as a wound dressing alternative, for the treatment of skin lesions. The hydrogels were prepared using free radical polymerization, and were characterized using scanning electron microscopy, infrared spectroscopy, thermogravimetry, differential scanning calorimetry, swelling capacity, mechanical and rheological properties, UV-Vis spectroscopy, antioxidant activity by the DPPH, ABTS and FRAP assays and biocompatibility determined in Vero cells and J774 macrophages by the MTT assay. Hydrogels showed a porous and foliaceous structure with a well-defined network, a good ability to absorb water and aqueous solutions simulating body fluids as well as desirable mechanical properties and pseudoplastic behavior. In hydrogels containing 1.0 and 2.5% propolis, the contents of total polyphenols were 24.74 ± 1.71 mg GAE/g and 32.10 ± 1.01 mg GAE/g and those of total flavonoids 8.01 ± 0.99 mg QE/g and 13.81 ± 0.71 mg QE/g, respectively, in addition to good antioxidant activity determined with all three methods used. Therefore, hydrogels containing propolis extract, may serve as a promising alternative wound dressing for the treatment of skin lesions, due to their anti-oxidant properties, low cost and availability.